The Effect of Administrative Service Quality and Officer Responsiveness on Service Satisfaction - Sitti Husna Noviana Djou; Darman Darman; Celsi Kuku (Westscience Press, 2023)
This research was conducted to determine the quality of administrative services and officer responsiveness to the service satisfaction of the Bakida Village Office in Gorontalo. The sampling technique used was Accidental Sampling by determining 76 respondents. The research method uses quantitative descriptive with the Statical program for socian science (SPSS). The results of this study show that the Quality of Administrative Services and Officer Responsiveness significantly affect Service Satisfaction at Village Offices with a calculated F value of 103,706, with the number of influences of 0.737 or 73.7%. The quality of administrative services has a significant effect on Service Satisfaction at the Village Office with a calculated value of 3,445, Officer Responsiveness has a significant effect on Service Satisfaction at the Village Office with a calculated value of 6.412.